Prognostic value of long non-coding RNAs in triple negative breast cancer: A PRISMA-compliant meta-analysis - Zhang, Shuo (Medicine (Baltimore), 2020)
BACKGROUND: Triple-negative breast cancer (TNBC) is the most aggressive and lethal subtype of breast cancer. Accumulating evidence showed long non-coding RNAs (lncRNAs) are abnormally expressed in TNBC and could be valuable prognostic tools for TNBC patients. This study aims to research the prognostic value of lncRNAs in TNBC, using the meta-analysis method. METHODS: We performed a detailed literature search on Pubmed, Scopus, and Web of Science for studies on the prognostic value of lncRNAs in TNBC. The meta-analysis method was used to determine the relationship between lncRNAs expression and survival of TNBC patients. RESULTS: A total of 2803 TNBC patients and 24 lncRNAs from 27 different articles were included in the present study. Subgroup analysis demonstrated that overexpression of lncRNAs in a group that is upregulated in TBNC showed a significant association with poor overall survival (HR = 1.86, 95%CI = 1.45–2.27, I(2) = 41.9%) and disease-free survival (HR = 1.85, 95%CI = 1.37–2.33, I(2) = 0%). Conversely, overexpression of lncRNAs in a downregulation group was markedly related to good overall survival (HR = 0.60, 95%CI = 0.43–0.77, I(2) = 28.6%). Moreover, expression of lncRNA SNHG12, MALAT1, HOTAIR, HIF1A-AS2, HULC, LINC00096, ZEB2-AS1, LUCAT1, and LINC000173 showed a marked correlation with positive lymph node metastasis (LNM), while lncRNA MIR503HG, GAS5, TCONS_l2_00002973 showed the opposite effect. High expression level of MALAT1, HIF1A-AS2, HULC, LINC00096, ADPGK-AS1, ZEB2-AS1, LUCAT1 were positively correlated with distant metastasis (DM), while lncRNA MIR503HG showed the opposite effect. In addition, the mechanisms of lncRNAs in TNBC were summarized. CONCLUSIONS: This meta-analysis demonstrated that abnormally expressed lncRNA were significantly associated with the survival of TNBC patients and may serve as biomarkers and therapeutic targets for TNBC prognosis.